EVALUACIÓN FINANCIERA EN LA IMPORTADORA ESPINOSA SEGARRA DE LA CIUDAD DE LOJA, EN EL PERÌODO 2012 - Ulloa Quezada, María fernanda (2015)
The thesis called "financial assessment into the importing ESPINOSA SEGARRA LOJA CITY IN THE PERIOD 2012," development is the adherence to the general objective is to "ensure the financial evaluation in the importing Espinosa Segarra City Loja In the period 2012 ", by the application of methods and techniques to verify the truthfulness, accuracy and authenticity of profitability, to be an ideal tool for improving financial management, it gives the same performance under the following specific objectives. To fulfill the first objective is to determine the economic situation of the company in the period established in order to meet the productivity of capital invested, the development is by applying the vertical analysis to determine the actual economic and financial situation of the company where the degree was determined percentage of participation of each of the items in this economic period. The second objective financial indicators such as liquidity, turnover, leverage, and profitability was applied; where it was learned that the importing Espinosa maintains a liquidity Segarara $ 37.34 inventory turns 1.72 times as well as a debt of 25.16% and net profit margin of 10.65%, and same performance equity of 14.15%, in order to determine the effectiveness and efficiency of the activities performed by the 5 administrative part of the Importer, the same that were plotted and interpreted. For the third objective of the Index Value Added EVA it is used, in order to determine whether the net income is sufficient to cover the obligations they generate loans made and the expectations of the owner, based on measurable values, which are presented in Financial Statements as Statement of Financial Position, and Income Statement, being considered a powerful tool that allows to know if a company creates or destroys value for its owner. The methodology helped determine the rate of return on equity denotes a representative for the company's 14.15% value, which means that the owner posted a return on their investment, and the return on assets with a value 10.59% of this value is favorable for the company, since the return on assets is efficient. Finally the results obtained that the importing Espinosa Segarra has made no Financial Assessment so it is recommended that the owner make a financial assessment annually and to take corrective actions to the development of the importing actions based concludes.